The reality of electronic administration and its role in the efficiency of the performance of government health institutions from the point of view of a sample of administrators and health cadres in the city of Riyadh - Al-Anzi, Abdullah Suleiman; Al-Otaibi, Iqab Mishal; Al-Qafary, Ahmed Ali; Al-Otaibi, Saleh Kitab (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the reality of electronic management in government health institutions in Riyadh, and its relationship to the efficiency of the performance of government health institutions in Riyadh from the point of view of a sample of administrators and health cadres in the city of Riyadh. In health institutions in the government sector in the city of Riyadh, their number is (281). The results showed that the tool’s general obtained a total average (3.70 out of 5) and at the level of the two axes; The reality of electronic administration got a total average of (3.74 out of 5), and the efficiency axis of the performance of health institutions in the city of Riyadh got an average of (3.66). Both of them are at a (high) degree. The results also showed a positive direct relationship that amounted to (0.89) and reflects a (large) and statistically significant relationship at the level (0.05) between electronic management and raising the efficiency of government health institutions in Riyadh. As well as the absence of statistically significant differences at the level (0.05) between the average answers of the study sample about the role of electronic management in raising the efficiency of the performance of government health institutions in Riyadh due to the variables (type of job, number of years of experience). In light of the results, the researchers recommended the necessity of hospitals in the government health sector in Riyadh to automate medical records and information related to patients electronically through electronic archiving, with the possibility of referring to them at any time. And the need for hospitals to pay attention to the government health sector in Riyadh with continuous training of administrators and health cadres. And the need to develop the administrative structure in the government health sector hospitals in Riyadh so that it fits with the electronic management method. The study also suggests studying the impact of electronic management on patient satisfaction in government health institutions in Riyadh. And the study of the physical, technical and organizational factors affecting the performance of electronic management in government health institutions in the city of Riyadh.